Supercomputer Modeling of Dual-Site Acetylcholinesterase (AChE) Inhibition - Lushchekina, Sofya V.; Makhaeva, Galina F.; Novichkova, Dana A.; Zueva, Irina V.; Kovaleva, Nadezhda V.; Richardson, Rudy R. (Supercomputing Frontiers and Innovations, 2018)
Molecular docking is one of the most popular tools of molecular modeling. However, in certain cases, like development of inhibitors of cholinesterases as therapeutic agents for Alzheimer’s disease, there are many aspects, which should be taken into account to achieve accurate docking results. For simple molecular docking with popular software and standard protocols, a personal computer is sucient, however quite often the results are irrelevant. Due to the complex biochemistry and biophysics of cholinesterases, computational research should be supported with quantum mechanics (QM) and molecular dynamics (MD) calculations, what requires the use of supercomputers. Experimental studies of inhibition kinetics can discriminate between dierent types of inhibition—competitive, non-competitive or mixed type—that is quite helpful for assessment of the docking results. Here we consider inhibition of human acetylcholinesterase (AChE) by the conjugate of MB and 2,8-dimethyl-tetrahydro-y-carboline, study its interactions with AChE in relation to the experimental data, and use it as an example to elucidate crucial points for reliable docking studies of bulky AChE inhibitors. Molecular docking results were found to be extremely sensitive to the choice of the X-ray AChE structure for the docking target and the scheme selected for the distribution of partial atomic charges. It was demonstrated that exible docking should be used with an additional caution, because certain protein conformational changes might not correspond with available X-ray and MD data.